Hubungan Sarapan Pagi Dengan Status Gizi dan Hasil Belajar Pada Murid SD Negeri No. 5 Tonja Denpasar Utara Provinsi Bali - Ida Ayu Gede Dwi Laksmi Dewi; I Komang Agusjaya; I Made Rodja Suantara (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2019)
Based on Basic Health Research (2010), there are 35.000 school-age children, around 26,1% have breakfast just with mineral water and 44,6% get energy income less than 26,1% of nutritional needs in a day. The purpose of this research is to know the relation between breakfast with nutrition status and learning results of students in Primary School No. 5 Tonja North Denpasar. The type of the research is observational research with a crossectional design, with a total sample are 63 people. breakfast consumption data was collected using recall methods, and Nutrition status data based on indicators (IMT/U) was collected using the recording method of learning results from each student. Data processed by statistic analysis Korelasi Pearson. The result of the research shows that the average breakfast type is 2 types, for example, bread and milk. The type of breakfast that is mostly consumed are 2 types with the minus category that 28 samples (44,4%), energy consumption level 28 samples (44,4%) normal category, and protein consumption level 30 sample (47,6%) normal category. Normal nutritional status 45 samples (71.4%), lean 1 sample (1.6%), grease 7 samples (11.1%), obesity 10 samples (15.9%). The average learning result is enough for category 51 samples (81,0%). There is no relationship between breakfast with nutritional status and learning outcomes (p 0.05).Keywords: Breakfast, Energy and Protein Consumption, Nutritional Status, Learning Outcomes